Application of Array CGH on Archival Formalin-Fixed Paraffin-Embedded Tissues including small numbers of microdissected cells - Johnson, Nicola (2006)
Array-based comparative genomic hybridisation (aCGH) has diverse applications in cancer gene discovery and translational research. Currently, aCGH is performed primarily using high molecular weight DNA samples and its application to formalin-fixed and paraffin-embedded (FFPE) tissues remains to be established. To explore how aCGH can be reliably applied to archival FFPE tissues and whether it is possible to apply aCGH to small numbers of cells microdissected from FFPE tissue sections, we have systematically performed aCGH on 15 pairs of matched frozen and FFPE glioblastoma tissues using a well established in-house human 1Mb BAC/PAC genomic array. By spiking glioblastoma DNA with normal DNA, we demonstrated that at least 70% of tumour DNA was required for reliable aCGH analysis. Using aCGH data from frozen tissue as a reference, it was found that only FFPE glioblastoma tissues that supported PCR amplification of >300bp DNA fragment provided high quality, reproducible aCGH data. The presence of necrosis in a tissue specimen had an adverse effect on the quality of aCGH, while fixation in formalin for up to 96 hours of fresh tissue did not appear to affect the quality of the result. As little as 10-20ng DNA from frozen or FFPE tissues could be readily used for aCGH analysis following whole genome amplification. Furthermore, as few as 2000 microdissected cells from haematoxylin stained slides of archival FFPE tissues could be successfully used for aCGH investigations when whole genome amplification was used. By careful assessment of DNA integrity and review of histology, to exclude necrosis and select specimens with a high proportion of tumour cells, it is feasible to pre-select archival FFPE tissues adequate for aCGH analysis. With the help of microdissection and whole genome amplification, it is also possible to apply aCGH to histologically defined lesions, such as carcinoma in situ.